CONSUMER PROTECTION FROM ILLEGAL COSMETIC PRODUCTS ACCORDING TO ISLAMIC LAW: A STUDY ON THE ACEH FOOD AND DRUG MONITORING AGENCY (BPOM), INDONESIA - Kartika Dwi Novasari; Fithria, Nurul (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2024)
This article aims to analyse a consumer protection in cosmetic products that are not registered with Food and Drug Administration (Badan Pengawas Obat dan Makanan, BPOM). It uses the normative-juridical research methods with a statutory approach. The results shows that Indonesia has a legal relating to consumer protection, namely Law Number 8 of 1999 concerning Customer Protection. Thus, any fraudulent businesses actors who still frequently violate statutory regulations can be subject to sanctions in the form of administrative or criminal sanctions. Additionally BPOM as a supervisory agency also actively monitors the circulation of this dangerous product and even withdraws the product if it is proven to contain dangerous ingredients. Similarly, in the context of Islamic law, this supervision is strengthened by the principles of justice, responsibility and protection of consumers. Islamic law‘s objective is to ensure that cosmetic products on the market meet the safety standards set by Islamic principles, as well as providing appropriate protection to consumers fro